Finding Baseline Parameters Of The Neurodynamic Test of The Upper And Lower Limbs: False Positive Rate Among Healthy Asymptomatic Adult (International Journal of Physiotherapy, 2024)
Background: Neurodynamic tests are used by most physiotherapists in clinical examinations to differentiate the underlying pathoanatomic structures. We examined the false positive rate of upper limb neural tension test (ULTT) & seated slump test (STT) in healthy individuals with no history of any cervical & lumbar symptoms. To form baseline parameters to differentiate between normal and actual pathology.Methods: An observational cross-sectional study. Ninety-eight subjects participated, with 49 males & 49-female with mean ages of twenty-two 22.28 & 20.53 respectively. The test methods used were ULTT and SST. Tester 1 performed the test. Tester 2 was blinded & measured the range of motion employing universal goniometry.Results: The mean elbow extension for ULTT-R was 32.67 with 95% C. I between 30.38° to 34. 89°. And for ULTT-L, it was 34.75° with a 95% CI between 32.61 to 36.89. The mean knee extension for SST-R was 15.92° with 95% C. I between 12.81 to 19.03. And SST-L was 14.27 with 95 % C. I was between 11.51 to 17.04. To increase ULTT and SST's diagnostic accuracy, clinicians can use these results to establish baseline criteria for identifying pathological and non-pathological findings.Conclusion: Based on the 75th Percentile, we suggested that a positive test only be identified when peripheral symptoms are reproduced before 20° of knee extension on the right and 18° on the left side and elbow extension before 45° on the right and 41° on the left side.